Comparison of the acute effects of traditional and reaction-based HIIT on brain connectivity and cognitive responses - Çagin, M.; Cicioglu, H. I.; Ertan, H. (BMC Sports Science, Medicine and Rehabilitation, 2025)
The aim of this study is to comparatively investigate the acute effects of traditional and reaction-based HIIT (High Intensity Interval Training) methods on brain connectivity and cognitive responses. A total of 33 athletes (17 female, 16 male), 3 from each of the elite shooting, badminton, basketball, gymnastics, football, softball, karate, taekwondo, tennis, swimming and volleyball branches, were included in the study. The average age of the athletes included in the study was 21.4 ± 1.8 years and the average sports history was 9.4 ± 2.9 years. The athletes were equally and randomly distributed to traditional HIIT (11), reaction-based HIIT (11) and control groups (11). First, 2-min eyes-open resting EEG recordings were taken from the athletes. After the resting records, the Stroop Test consisting of 100 images (50% compatible) was applied in a computer environment and EEG records were taken simultaneously. The athletes applied a 5-min run and warm-up exercises. At the end of the warm-up period, the athletes applied 10 min of HIIT according to their groups. After the completion of HIIT, rating of perceived exertion was applied to determine the perceived exertion. Finally, the Stroop post-tests simultaneously with the EEG of all groups were taken and the measurement process was completed. All measurements related to the research were carried out at 23.1 °C (± 0.17) ambient temperature in Gazi University, Faculty of Sports Sciences Wrestling Hall. Three-way repeated measures ANOVA and independent groups T-Test were applied to the data obtained from the athletes in R and SPSS statistical programs. According to the obtained findings, significant differences were detected between the fronto-temporal, fronto-occipital, occipito-temporal regions in terms of connectivity and between the groups in terms of perceived difficulty level (p < 0.05). As a result of the research, in terms of brain connectivity; While the reaction-based HIIT method was observed to have positive effects on cognitive processes such as focused attention and decision-making skills by increasing synchronization especially in the fronto-temporal regions; it was observed that the traditional HIIT method decreased the perception of effort of the activity by decreasing the synchronization in the fronto-occipital region and contributed positively to the visual information processing processes by increasing the synchronization in the occipito-temporal region. In addition, although the heart rates of both groups were similar during HIIT, the reaction-based HIIT group perceived a higher level of difficulty than the traditional HIIT group. In the light of these results, it can be said that the use of applications that include unpredictability and variable environmental conditions, such as reaction-based HIIT, more in the development of athletic performance can make the applied training method more functional in cognitive terms.